Acute hepatitis of non-specified etiology - Ye. V. Tsyganova; O. O. Znoyko; N. D. Yushchuk; K. R. Dudina; M. G. Isagulyants; N. V. Petrakova; T. V. Petrova; M. I. Mikhaylov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
Aim of investigation. To estimate pathogenic and diagnostic value of detection of hepatotropic viruses components (DNA, RNA, antigens) and antiviral immune response at acute hepatitis of non-specified etiology by the methods of enzyme-linked immunoassay (EIA), polymerase chain reaction (PCR) and Т-cellular lymphocytes proliferation in response to HCV antigens stimulation.Methods. Overall 42 patients with acute hepatitis of not specified etiology (AHNSE) were included in original study. Thirty three patients with acute hepatitis C and 36 patients with acute hepatitis B made groups of comparison, control group included 15 healthy persons. Investigation of patients with acute hepatitis of non-specified etiology included clinical, epidemiologic, routine laboratory, serological methods; molecular biological method (RNA of hepatitis A, C, Е, G viruses; DNA of hepatitis B virus, TTV, CMV, EBV, HHV of 1, 2, 6 and 8 types, PV B-19, NV-f – qualitative analysis); method of immunofluorescence (assessment of antimitochondrial and antinuclear antibodies); immunologic methods (laboratory diagnostic methods) – independent assessment of specific antibodies for individual HCV antigens spectrum, including structural and unstructural proteins and compound peptides, representing the whole HCV polyprotein (overall 38 antigens: 34 HCV antigens and 4 control antigens) in blood serum by EIA method; investigation of Т-cellular immune response to HCV antigens by blast-cell lymphocytes transformation method under stimulation by HCV antigens with quantitative evaluation of cytokine secretion; instrumental method – ultrasound investigation of abdominal organs.Conclusions. As a result of the study within the group of patients with acute hepatitis, that never visited precinctive regions, viral hepatitis Е was revealed by EIA in 4,8% of cases, including 2,4% when it was detected both by EIA and PCR. It is possible to assume, that the portion of acute HCV-infection with atypical serological profile (according to commercial tests-systems data) reaches 17% of AHNSE patients, and at application of multiparametric diagnostic criterion, including 6 parameters, – 43,5%.